2021
DOI: 10.1186/s12864-021-08027-w
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of the nomenclatural type strain of the nematode-associated entomopathogenic bacterium Providencia vermicola

Abstract: Background Enterobacteria of the genus Providencia are mainly known as opportunistic human pathogens but have been isolated from highly diverse natural environments. The species Providencia vermicola comprises insect pathogenic bacteria carried by entomoparasitic nematodes and is investigated as a possible insect biocontrol agent. The recent publication of several genome sequences from bacteria assigned to this species has given rise to inconsistent preliminary results. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 113 publications
1
23
0
Order By: Relevance
“…Even though the phylogenetic position at the 16S rRNA sequence level suggests a separate branch for LLDRA6 T within Providencia (Fig. 1), bootstrap values on branches ranging from 50-80 %, indicate that the clade topology around LLDRA6 T is insufficiently supported, probably because of the high similarity in 16S rRNA sequences, which is in agreement with the previous statement of insufficient resolution of 16S rRNA phylogenies for species delineation in Providencia [2,10,13]. Hence, in the present case, more evidences are needed to support the hypothetical theory that strain LLDRA6 T is the representative of a novel species in Providencia.…”
Section: S Rrna Gene Phylogenysupporting
confidence: 90%
See 1 more Smart Citation
“…Even though the phylogenetic position at the 16S rRNA sequence level suggests a separate branch for LLDRA6 T within Providencia (Fig. 1), bootstrap values on branches ranging from 50-80 %, indicate that the clade topology around LLDRA6 T is insufficiently supported, probably because of the high similarity in 16S rRNA sequences, which is in agreement with the previous statement of insufficient resolution of 16S rRNA phylogenies for species delineation in Providencia [2,10,13]. Hence, in the present case, more evidences are needed to support the hypothetical theory that strain LLDRA6 T is the representative of a novel species in Providencia.…”
Section: S Rrna Gene Phylogenysupporting
confidence: 90%
“…The species members of Providencia are mostly distributed in insects, invertebrates, vertebrates and humans [1][2][3][4][5][6]. Particularly, the majority of them are believed to be potentially pathogenic and can be frequently detected in human specimens of diarrhoea, urinary tract infections, wounds, burns and bacteraemia [13]. Recent studies have shown that bacterial strains within Providencia also inhabit heavy metal contaminated soils [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Providencia spp. have been found in a variety of organisms, including birds, fish, and fruit flies, and can be isolated directly from water [ 13 , 14 , 15 , 16 , 17 ]. The discovery of bla NDM-1 in Providencia is concerning because these bacteria are naturally resistant to tetracycline and colistin, making the clinical treatment of these infections extremely difficult [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…
Providencia is a genus of Gram-negative bacteria belonging to the Morganellaceae family. This genus includes nine species (P. stuartii, P. sneebia, P. rettgeri, P. rustigianii, P. heimbachae, P. burhodogranariea, P. alcalifaciens, P. huaxiensis, and P. vermicola) with varying degrees of virulence, capable of infecting humans and insects [1,2].For Gram-negative bacteria, the somatic antigen (O-antigen) has become one of the key virulence factors. It is the highly immunogenic part of lipopolysaccharides due to the distal location.
…”
mentioning
confidence: 99%
“…Providencia is a genus of Gram-negative bacteria belonging to the Morganellaceae family. This genus includes nine species (P. stuartii, P. sneebia, P. rettgeri, P. rustigianii, P. heimbachae, P. burhodogranariea, P. alcalifaciens, P. huaxiensis , and P. vermicola ) with varying degrees of virulence, capable of infecting humans and insects [1, 2].…”
mentioning
confidence: 99%